2022
DOI: 10.3390/microorganisms10010191
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Phylotypes of White Spot Syndrome Virus in Bangladesh and Their Virulence

Abstract: White Spot Syndrome Virus (WSSV) has emerged as one of the most prevalent and lethal viruses globally and infects both shrimps and crabs in the aquatic environment. This study aimed to investigate the occurrence of WSSV in different ghers of Bangladesh and the virulence of the circulating phylotypes. We collected 360 shrimp (Penaeus monodon) and 120 crab (Scylla sp.) samples from the south-east (Cox’s Bazar) and south-west (Satkhira) coastal regions of Bangladesh. The VP28 gene-specific PCR assays and sequenci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Lysozyme release slowed down at pH 7 due to the exchanges between cationic muramidase and non-ionic API or Na-caseinate (Benelhadj et al, 2016). Hasan et al (2022) tested lysozyme in experimentally infected shrimps with different doses and with different phylogroups of the virus and observed variations in average relative expression between the infected shrimps with two groups of virus. Deris et al (2020) observed different patterns of lysozyme gene expressions in shrimp post-larvae (PL) after challenged with pathogenic microorganisms.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Lysozyme release slowed down at pH 7 due to the exchanges between cationic muramidase and non-ionic API or Na-caseinate (Benelhadj et al, 2016). Hasan et al (2022) tested lysozyme in experimentally infected shrimps with different doses and with different phylogroups of the virus and observed variations in average relative expression between the infected shrimps with two groups of virus. Deris et al (2020) observed different patterns of lysozyme gene expressions in shrimp post-larvae (PL) after challenged with pathogenic microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…RNA extraction kit (New England Biolabs, Ipswich, MA, USA) was utilized for extracting RNA from diseased and fresh shrimps. PhotoScript II First Strand cDNA Synthesis Kit, (New England Biolabs, Ipswich, MA, USA) was used for the synthesis of cDNA (Hasan et al, 2022).…”
Section: Preparation Of Samples Rna Extraction and Cdna Synthesismentioning
confidence: 99%
See 3 more Smart Citations